A President's Dream - Learn By Doing [float] - Cal Poly San Luis Obispo Audio-Visual Department::::::::: (1965)
A white float is pulled down the street in the Homecoming Parade. It says 'A President's Dream' on the side and has an outline of the state of California with the Cal Poly SLO and Pomona campuses plotted on it.